The relationship between serum 25-hydroxy vitamin D and blood pressure and quality of life in overweight and obese patients with type 2 diabetes mellitus compared with healthy subjects - Naser Aghamohammadzadeh; Neda Dolatkhah; Maryam Hashemian; Seyed Kazem Shakouri; Saeed Hasanpour (Babol University of Medical Sciences, 2020)
Background: Vitamin D is one of the known lipoprotein hormones with metabolic properties. We aimed to determine the serum 25-hydroxy vitamin D concentration in overweight/obese subjects with diabetes mellitus type Ⅱ (DM Ⅱ) in association with systolic and diastolic blood pressure and quality of life compared with healthy participants. Methods: The current case-control study was carried out among 80 overweight/obese subjects with DM Ⅱ, and 77 healthy subjects matched by sex, age and body mass index (BMI). Serum 25-hydroxyvitamin D concentration was measured by ELISA method. In order to examine the quality of life, the Persian version of SF36 questionnaire was used. Results: There was significant difference between diabetic and healthy subjects considering serum 25-hydroxyvitamin D concentration (p=0.012). Serum 25- hydroxyvitamin D concentration was inversely correlated with diastolic blood pressure (p=0.02) and positively associated with physical function (p<0.001), social function (p<0.001) and general health (p<0.001) components of quality of life in diabetic subjects and physical health sub-scale (p=0.004) in all participants. Conclusion: Serum 25-hydroxyvitamin D concentration was significantly lower in diabetic subjects in comparison with healthy controls. There was a significant reverse relationship between serum concentrations of 25-hydroxyvitamin D with diastolic blood pressure and on the other hand, a significant positive relationship with physical function, social function and general health components and physical health subscale of quality of life in participants with DM Ⅱ